Partial liver volume radioembolization induces hypertrophy in the spared hemiliver and no major signs of portal hypertension. Issue 3 (27th March 2013) - Fernández‐Ros, Nerea; Silva, Nuno; Bilbao, Jose Ignacio; Iñarrairaegui, Mercedes; Benito, Alberto; D'Avola, Delia; Rodriguez, Macarena; Rotellar, Fernando; Pardo, Fernando; Sangro, Bruno
Abstract Background Post‐treatment contralateral hemiliver hypertrophy has created an interest in lobar liver radioembolization (RE) as a pre‐surgery tool. Methods Liver and spleen volumes and function were studied in 83 patients submitted to partial liver volume RE at 4–8 weeks (T1), 10–26 weeks (T2), and >26 weeks (T3) after RE. Results More than half of the patients had cirrhosis with hepatocellular carcinoma. The main finding was a progressive increase in the volume of the spared hemiliver (mean absolute increase at T3: 230 ml). The percentage of patients in whom the baseline ratio of spared volume to total liver volume was <40% dropped from 56.6% at baseline to 29.4% at T2 (P < 0.001). A significant and progressive increase in spleen volume but not in portal vein diameter was also observed. A small percentage of patients developed hypersplenism, mostly those without cirrhosis (16.0% at T2). Six patients (five with portal vein thrombosis, cirrhosis or both) developed signs of portal hypertension by T2. Conclusions The present results warrant further studies to better elucidate the mechanism underlying this phenomenon of spared hemiliver hypertrophy and to investigate its role as an alternative to portal vein embolization in the management of patients with potentially resectable liver tumours.